Cyberbullying from the student's perspective: "what we live, see and do" - Chaves-Álvarez, Ana Lucía (2020)
The present work is derived from the research "Cyberbullying: knowing its impact on the socio-emotional development of the adolescent population and reflecting on possible ways to prevent it", which took into account the opinion of adolescents, teachers, directors and parents. The article focuses on the perception of cyberbullying by adolescents. Therefore, its goal is to report the opinions of students about the concept, roles, impact and actions taken by adults regarding this social phenomenon. The study has a mixed-type approach, exploratory and descriptive, of the impact that cyberbullying has on the socio-emotional development of the adolescent. Answers were obtained from 447 students from 7th to 11th grade, in an age range of 12 to 19 years old, from 4 secondary schools, located in the provinces of Heredia and San José, Costa Rica, intentionally selected, after coordination with authorities and parents to obtain the respective endorsements. The information was obtained through a questionnaire with open-ended and closed-ended questions and was analyzed from the quantitative and qualitative perspective, including emerging categories elaborated from the answers provided. The most notable results show that the majority of students use cybernetic and technological tools in school and at home, without adult supervision. Bullying occurs in 23.7% of students in 7th to 9th grades, and in 16.9% of students in 10th and 11th grades. The most widely used means of harassment are Facebook, text messages and telephone calls, mainly affecting the socio-emotional health, due to the fear, insecurity and distrust experienced. According to the researchers, it could be concluded that the harassment suffered by this adolescent population is not typified as Cyberbullying, because most victims know the identity of the harasser, not fulfilling the main characteristic s this problem, which is anonymity. The study is based on a warning for families, teachers and caregivers, regarding the role they should play in the lives of adolescents, the types of relationships they establish, and the socio-emotional needs of this population.